The effect of ZnO (zinc oxide) and glycerol concentrations on the mechanical properties of bioplastics made from Canna tuber (Canna edulis) starch - Tanalyna Hasna; Cinta Ayu Lestari; Widya Dwi Rukmi Putri; Vivien Fathuroya (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2022)
The problem of plastic waste in Indonesia is increasingly worrying due to its long degradation duration. Bioplastics made from starch are easily degradable in nature and have a lower contribution to environmental pollution. This study aimed to determine the effect of ZnO and glycerol additions on the thickness, tensile strength, elongation, Young’s Modulus, water absorption, and biodegradation of bioplastics. The results indicate that adding ZnO and glycerol has significant effects on thickness, tensile strength, elongation, Young’s Modulus, water absorption, and biodegradation. A high concentration of ZnO and glycerol was parallel to an increase in the thickness of bioplastic. A high ZnO concentration and low glycerol concentration increases the tensile strength and Young’s Modulus, but decreases the water absorption. Glycerol at high concentration and ZnO at low concentration increases the elongation. The addition of ZnO in a small amount positively affects the biodegradation of bioplastics.